The effects of short-term high-intensity interval training vs. General interval training in rugby players - Liu, C. M. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: High-intensity interval training (HIIT) is one of the training methods which designed to optimize the athletic performance through variety exercise type with high exercise intensity, less recovery time (interval), and several bouts. It has been found varying HIIT doses were effective, but there is no indication of the different effects between the short term HIIT and general interval training. The purpose of this study was to investigate the different effects of short-term HIIT and general interval training on speed, power, agility, and endurance of rugby players.